A uniaxial tensile behavior based fatigue crack growth model. (February 2020) - Wu, S.C.; Li, C.H.; Luo, Y.; Zhang, H.O.; Kang, G.Z.
Highlights: Critical fatigue damage value was validated with limited impact on FCG predictions. FCG rate can be well formulated via uniaxial tensile behavior of metallic materials. Compared with NASGRO equations and experimental data, the newly-developed iLAPS model can achieve better precision under broad stress ratios. Abstract: Metallic components fail mostly due to fatigue cracks, and thus a suitable non-destructive detection is necessarily planned to ensure the operation safety. Among the requisite parameters, a fatigue crack growth (FCG) model might be the most important input, which is frequently acquired from well-defined and expensive fracture mechanics experiments. By correlating the uniaxial tensile properties (UTP) with cyclic plastic parameters and developing a unified fatigue crack closure factor U suitable for broad stress ratios, a novel FCG model of improved LAPS (iLAPS) was formulated in terms of linear damage accumulation and Rice-Kujawski-Ellyin field. Results show that the newly-developed iLAPS model can simulate the entire crack growth region as like modified NASGRO does. For open-reported structural materials available with both UTP and FCG data, it is found that current iLAPS predictions are well agreed with experimental results and are also better than original LAPS.